The beloved disciple : following John to the heart of Jesus - Moore, Beth, 1957-; McCleskey, Dale (Nashville. Te.. Broadman & Holman Publishers, 2003)
The Beloved Disciple" is the trade book adaptation of the bestselling, video-based, interactive Bible study "Beloved Disciple." It shows readers that John was uniquely chosen to be the one who received the Revelation of Jesus Christ, and that Christ still desires to reveal Himself to His disciples today.
pt. 1. Fresh winds over Galilee -- pt. 2. Sights and insights -- pt. 3. Defining moments -- pt. 4. Beyond the limits -- pt. 5. Receiving His fullness -- pt. 6. Life more abundantly -- pt. 7. Letters from the heart -- pt. 8. Among the lampstands -- pt. 9. From a throne's-eye view -- pt. 10. Blessed benediction.
Includes bibliographical references (pages 336-340).
Keywords: Jesus Christ; John, -- the Apostle, Saint; Beloved Disciple; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Christian life; Nonfiction; Commentaries; Criticism, interpretation, etc; Commentaries